1995
DOI: 10.1111/j.1553-2712.1995.tb03278.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury as a Motivator to Reduce Drinking

Abstract: Objectives: To identify predictors of readiness to change drinking behavior by minor-injury patients who had positive saliva alcohol tests (SATs) in the ED. To develop and test a model intended to be prognostic of readiness to change, which included predispositional and injury-event-related variables.Methods: An on-site survey was conducted of minor-injury ED patients sampled consecutively during predesignated periods. Patients were identified as SAT-positive during their screening evaluations. After giving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 10 publications
8
115
2
4
Order By: Relevance
“…Longabaugh and colleagues have deemed events that draw an association between substance use and adverse health events "teachable moments" in which patients may be more motivated to change their harmful behaviors (Longabaugh et al, 1995). Brief interventions to enhance motivation after an alcohol-related event have been implemented in emergency room and hospital settings with some success (D'Onofrio and Degutis, 2002;Dunn and Ries, 1997;Gentilello et al, 1999;Longabaugh et al, 2001;Wright et al, 1998) but few have extended this interventional approach to include drug-related events (Bernstein et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Longabaugh and colleagues have deemed events that draw an association between substance use and adverse health events "teachable moments" in which patients may be more motivated to change their harmful behaviors (Longabaugh et al, 1995). Brief interventions to enhance motivation after an alcohol-related event have been implemented in emergency room and hospital settings with some success (D'Onofrio and Degutis, 2002;Dunn and Ries, 1997;Gentilello et al, 1999;Longabaugh et al, 2001;Wright et al, 1998) but few have extended this interventional approach to include drug-related events (Bernstein et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In addition, offering feedback about specific risks or consequences of their drinking to patients who drink heavily can help motivate them to decrease alcohol consumption or seek treatment. 15,16 Physicians report they would be more likely to advise patients about safe drinking practices if they were more confident of their knowledge about safe levels of alcohol consumption. 17 Women who drink more than two drinks daily on average, or who frequently drink five or more drinks on one occasion, are at increased risk of alcohol dependence.…”
Section: Ess Than Three Quarters Of Women In the Unitedmentioning
confidence: 99%
“…Longabaugh et al [54] showed that the patient's injury and the perceived level of its association with substance use are predictive of readiness to change behavior. Warburton et al [70] have suggested that oral and maxillofacial surgeons are in a prime position to identify alcohol-related assault victims and ensure a coordinated multi-agency response to enhance the victims' chances of receiving comprehensive care and empathetic and informed assistance.…”
Section: Integrating the Surgeon Into Collaborative Carementioning
confidence: 99%
“…[52] Patients hospitalized after a substancerelated injury have been found to be motivated to change their drinking, [53] with aversiveness of the injury and perception of degree of substance involvement predictive of their level of motivation. [54] This ambivalence presents an opportunity for moving some patients towards behavior change.…”
Section: Lack Of Patient Motivation For Substance Use Treatmentmentioning
confidence: 99%